2022
DOI: 10.1007/s00330-022-08949-3
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative pelvic MRI and 2-[18F]FDG PET/CT for lymph node staging and prognostication in endometrial cancer—time to revisit current imaging guidelines?

Abstract: Objective This study presents the diagnostic performance of four different preoperative imaging workups (IWs) for prediction of lymph node metastases (LNMs) in endometrial cancer (EC): pelvic MRI alone (IW1), MRI and [18F]FDG-PET/CT in all patients (IW2), MRI with selective [18F]FDG-PET/CT if high-risk preoperative histology (IW3), and MRI with selective [18F]FDG-PET/CT if MRI indicates FIGO stage ≥ 1B (IW4). Methods In 361 EC patients, preoperative stagin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…A recent study of Fasmer et al demonstrated how selective use of 18-FDG PET-CT scan in patients with increased risk of extended EC, based on MRI (i.e., LNM, DMI, or CI) could be incorporated. Unfortunately, CA125 was not available in this study cohort, which might be interesting to add in future refined diagnostic work-up strategies [7]. Interestingly, elevated CA125 was significantly associated with the presence of LVSI, and thus could serve as a surrogate biomarker given its association with LNM in the multivariate analysis.…”
Section: Results In the Context Of Published Literaturementioning
confidence: 90%
See 1 more Smart Citation
“…A recent study of Fasmer et al demonstrated how selective use of 18-FDG PET-CT scan in patients with increased risk of extended EC, based on MRI (i.e., LNM, DMI, or CI) could be incorporated. Unfortunately, CA125 was not available in this study cohort, which might be interesting to add in future refined diagnostic work-up strategies [7]. Interestingly, elevated CA125 was significantly associated with the presence of LVSI, and thus could serve as a surrogate biomarker given its association with LNM in the multivariate analysis.…”
Section: Results In the Context Of Published Literaturementioning
confidence: 90%
“…As the risk of LNM in grade 3 EC varies between 15-44% depending on the histological subtype and myometrial invasion (MI), determination of lymph node status by lymphadenectomy or sentinel node (SN) biopsy is recommended in patients without clinical suspicion of advanced stage EC [2][3][4][5]. In the preoperative work-up abdominal computed tomography (CT), pelvic magnetic resonance imaging (MRI), and 18FDG positron emission tomography (PET)-CT can be considered to detect extra-uterine tumor spread or distant metastases, as this may impact the surgical approach [2,3,6,7]. After primary surgico-pathological staging, information about tumor stage, histopathological subtype, tumor grade, presence of deep myometrial invasion ≥50% (DMI), cervical stromal invasion (CI), lymphovascular space invasion (LVSI), or LNM guides adjuvant radiotherapy and/or chemotherapy [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…A similar approach was tested by Fasmer et al using pre-operative biopsy and pelvic MRI in all patients, with selective FDG-PET-CT based on high-risk MRI features (myoinvasion ≥50% and/or cervical stromal invasion and/or suspicious lymph nodes). 109 Based on their findings, pre-operative FDG-PET-CT only in cases with high-risk MRI features seems to bring the most benefit in detecting distant spread while avoiding unnecessary FDG-PET-CT-related radiation in low-risk patients.…”
Section: Reviewmentioning
confidence: 98%
“…A meta-analysis to determine FDG-PET/CT accuracy in diagnosing recurrent disease in endometrial cancer patients concluded with 95.8% sensitivity and 92.5% specificity for this modality [50]. Fasmer et al demonstrated that PET/CT has better detection of lymph node metastasis in high-risk patients than MRI, with a sensitivity and specificity of 56% and 90%, respectively [51]. However, a single-centered prospective study by Stewart et al aimed to determine PET/CT accuracy and determined that the high false negative rate (54.2%) proves that PET/CT alone should not be used to rule out lymph node metastasis.…”
Section: Positron Emission Tomography/computed Tomography (Pet/ct)mentioning
confidence: 99%